2020
DOI: 10.1089/can.2019.0047
|View full text |Cite
|
Sign up to set email alerts
|

Sex and Strain Variation in Initial Sensitivity and Rapid Tolerance to Δ9–Tetrahydrocannabinol

Abstract: Background and Objectives: For cannabis and other drugs of abuse, initial response and/or tolerance to drug effects can predict later dependence and problematic use. Our objective is to identify sex and genetic (strain) differences in initial response and rapid tolerance to D9-tetrahydrocannabinol (THC), the main psychoactive ingredient in cannabis, between highly genetically divergent inbred mouse strains-C57BL/6J (B6) and DBA/2J (D2). Experimental Approach: Sex and strain responses relative to baseline were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 81 publications
1
19
0
Order By: Relevance
“…[60] in ABH mice. The relatively smaller hypothermic effect observed here (Figure 3G-I) could represent a difference in mouse strain (ABH vs. C57BL/6J) [58,61]. Interestingly, in our study tolerance developed differently between behaviors, as 10 mg/kg of CB-13 continued to produce catalepsy but not tail-flick antinociception on day 3 of dosing (Figure 3B,E).…”
Section: Discussionmentioning
confidence: 54%
“…[60] in ABH mice. The relatively smaller hypothermic effect observed here (Figure 3G-I) could represent a difference in mouse strain (ABH vs. C57BL/6J) [58,61]. Interestingly, in our study tolerance developed differently between behaviors, as 10 mg/kg of CB-13 continued to produce catalepsy but not tail-flick antinociception on day 3 of dosing (Figure 3B,E).…”
Section: Discussionmentioning
confidence: 54%
“…Previously, we identified putative heritable strain differences in acute response to a single THC injection (10 mg/kg) in the parents of the BXD family—B6 and D2 (Parks et al 2020). Here we test the hypothesis that polymorphic variants between these strains segregate among the BXD progeny and cause variation in THC initial responses.…”
Section: Resultsmentioning
confidence: 99%
“…Each formulation was used for the entire testing schedule of each cohort (see details below). Previously we demonstrated that each THC formulation contains 95.2% of the initial amount of THC when measured eight days after preparation (Parks et al 2020).…”
Section: Methodsmentioning
confidence: 98%
See 2 more Smart Citations